THE EFFECTS OF LINGUISTIC INTELLIGENCE AND INTERPERSONAL COMMUNICATION COMPETENCE TOWARD STUDENTS’ ENGLISH SPEAKING SKILL - Sumarta Sumarta (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2016)
The purpose of this research is to know: 1.The effect of linguistic intelligence on English students’ speaking skill, 2. The effect of interpersonal communication competence on students’ English speaking skill, and 3. The effects of linguistic intelligence and interpersonal communication competence collaboratively on English students’ speaking skill. The method used in this research is quantitative. To collect the data of this research, writer uses interview and questionnaire. Interview is used for collecting the data of students’ speaking skill, and questionnaires are used to collect the data of linguistic intelligence and interpersonal competences. The participants of this research are 30 students, the English department students in the third semester at University of Singapebangsa Karawang, as the sample taken randomly from the number of students consisted of about 180 students. The result of the research showed that the effect of linguistic intelligence and interpersonal communication competence collaboratively toward students’ speaking skill with the regression Formula : ? = -2.448+0.607X1+0.379X2.  Keywords: Linguistic Intelligence, Interpersonal Communication Competence,                   Students’ English Speaking Skill.